ISLAMIC MICROFINANCE AS A TOOL FOR WOMEN EMPOWERMENT AND SUSTAINABLE ECONOMIC DEVELOPMENT GOALS IN BANGLADESH - Alam, Md. Shahbub; Uddin, Md. Kamal; Ali, Md. Jafor; Huda, Md. Nazmul; Bhuiyan, Abul Bashar (American International Journal of Multidisciplinary Scientific Research, 2022)
Bangladesh is now playing a role model in conventional microfinancing programs in the whole world. Though the financial sectors of this country cover both conventional and Islamic modes. There exist some limitations of conventional microfinancing operating by NGOs. The Islamic microfinancing programs are not enhanced in comparing conventional microfinancing due to a lack of proper policy formulation. Most people are practicing Muslims and want to avoid interest. The Islamic financial institutions have emphasized women’s empowerment through shariah-based microfinancing and achieving sustainable economic development. The main objective of this study is to investigate the effectiveness of Islamic microfinance for empowering women and achieving SDGs in Bangladesh. The methodology of this study is based on secondary data including existing relevant literature and annual reports of different financial institutions. The findings of this study show that Islamic microfinance institutions perform a significant role in empowering women as well as attaining SDGs and have a broader scope to flourish more by applying their various investment modes. This study will help to promote shariah-based microfinancing in the future and transmit microfinance systems to other countries of the world. This paper also tries to recommend some strategies and policy options to promote shariah-based microfinancing to reduce the challenges to ensuring women’s empowerment and attaining SDGs.